Pengaruh Dosis Pupuk Kandang Kambing terhadap Pertumbuhan dan Hasil pada Dua Varietas Kacang Panjang (Vigna unguiculata L.) - Rusmana, Azhar Indra; Budiasih, Rade; Widodo, R. Wahyono (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Poor choice of varieties and the decrease in soil fertility are among the few variables that can affect long peanut productivity. The aim of this research is to study how the dose of goat fertilizer and long bean varieties affects the growth and yield of long beans. The research was a factorial experiment with two factors and three replications using the Randomized Blok Design (RBD) method. The first factor, the dose of goat manure 0 ton ha-1(k0), 10 ton ha-1(k1), 20 ton ha-1(k2), 30 ton ha-1(k3), and 40 ton ha-1(k4). The second factor was long bean varieties Kanton Tavi (v1) and Katrina (v2). Data were analyzed using analysis of variance (ANOVA) at the 5% level. The results of the experiment showed an interaction in the parameters of plant height 7 DAP and 14 DAP, number of leaves 14 DAP, 21 DAP, 28 DAP, number of pods per plant, and pod weight per plot. A dose of 30-ton ha-1 (k3) goat pen fertilizer produced a healthy amount of beans on the cantonese Kanton Tavi variety (v1) with X optimum (v1) = 29,08 ton ha-1  and  Y maximum (v1) = 21,86 ton ha-1 and on Katrina variety (v2) X optimum (v2) = 25,15 ton ha-1 and maximum y (v2) = 20,56 ton ha-1.